Propensity score matched cohort study on magnesium supplementation and mortality in critically ill patients with HFpEF - Lijun Song; Jianjun Ying; Min Li; Lan Ying; Chenliang Zhao (Scientific Reports)
Abstract Heart failure with preserved ejection fraction (HFpEF) emerges as a singular subclass of heart failure, bereft of specific therapeutic options. Magnesium, an indispensable trace element, is essential to the preservation of cardiac integrity. However, the association between magnesium supplementation and mortality in HFpEF patients remains unclear. This study extracted HFpEF patient data from the MIMIC-IV database between 2008 and 2019. Propensity score matching was conducted to ensure that patients receiving magnesium supplementation (including magnesium sulfate and magnesium oxide) were balanced with those not receiving it in terms of baseline characteristics. The primary analysis focused on the 28-day all-cause mortality rate, with secondary endpoints encompassing ICU and one-year mortality rates, along with the duration of hospitalization. After matching, the study’s final cohort balanced at 1970 patients, with 985 patients per group. The results showed that magnesium intake significantly contributed to a decrease in the 28-day all-cause mortality rate (hazard ratio [HR], 0.682; 95% confidence interval [CI], 0.539–0.863), particularly in subgroups such as older patients (HR, 0.65; 95% CI 0.52–0.81), females (HR, 0.55; 95% CI 0.41–0.73), and those with hypertension (HR, 0.62; 95% CI 0.48–0.79) or without diabetes (HR, 0.54; 95% CI 0.41–0.71). Although magnesium treatment improved both ICU and one-year mortality rates, it concurrently resulted in extended ICU and hospital stays. Mediation analysis indicated that blood urea nitrogen partially mediated the association between magnesium intake and mortality, accounting for approximately 22.73% of the observed effect. Magnesium supplementation has illustrated a significant potential for mitigating the mortality rate in the HFpEF patient, particularly among the elderly, female, and individuals with hypertension. Therefore, magnesium supplementation stands as a potentially valuable supplementary treatment modality for patients with HFpEF. Further comprehensive research is warranted to explore its effects more deeply.